Interactive quiz media based on the Kahoot educational game to increase student motivation and learning outcomes - Latifah, Aslihatul; Choirudin, Choirudin; Ningsih, Eka Fitria (Universitas Muhammadiyah Malang, 2024)
The aim of this research is to evaluate impact use of quiz media interactive educational game based on Kahoot motivation and achievement Study student before and after implementing the Kahoot game. This research uses method quantitative experimental, with variables being measured through tests, questionnaires, and interviews structured to ensure the data collected nature numeric and can analyzed in a way statistics. This research also applies technique taking sample use cluster random sampling method. Data collection techniques involve use tests and questionnaires. Data analysis was carried out using analysis variance Multivariate using Wilk's Lambda test. Research results using test description of 5 pretests and 5 posttests in class VIII A Mts Mathla'ul Anwar Rawa Selapan show that Kahoot gaming media has a significant impact to enhancement motivation and results Study student. The results of MANOVA analysis show mark significance of 0.000 for Wilk's Lambda test, which is more small from level established significance​ previously. Hence, hypothesis​ zero rejected, implies that the use of Kahoot gaming media has a significant impact on motivation and results Study student